Python and Data Science: Building a Foundation with Practical Projects - Abduzzhohir, Yasir; Saleh, Muhammad Raihan; Sunatun, Sunatun; Saputra, Agita Irvanda; Wahyudi, Ramzy Al Firza; Hendra, Hendra; Mujiastuti, Rully; Sutrisno, Mirza; Jumail, Jumail; Rosanti, Nurvelly (Edumedia Solution, 2025)
In today's digital era, data has a crucial role in decision making. To increase public understanding, especially students, about Data Science, a webinar and online workshop titled “Python and Data Science: Building a Foundation with Practical Projects” through the Zoom Meeting Conference platform. This activity aims to provide a basic understanding of the concepts, benefits, and applications of Data Science in various industrial fields. Participants are invited to learn the use of Python in data analysis, and are given case study projects related to sales data analysis to apply the knowledge they have gained. This webinar and workshop activity was held on January 23, 2025, at 09.00 WIB which was attended by 40 participants from various institutions. The evaluation results show that participants expressed their satisfaction as indicated by the percentage of positive values in the feedback of 40% satisfied and 37% very satisfied with this activity. In addition, there was an increase in participants' understanding of Data Science, with the Pre-Test average score increasing from 7.87% to 8.21% on the Post-Test.